PERUBAHAN PERANAN BUNDO KANDUANG DALAM KEHIDUPAN MASYARAKAT MINANGKABAU MODERN - Sismarni Sismarni (Universitas Islam Negeri Imam Bonjol Padang, 2011)
Tradionally, the role of bundo kanduang is highly appreciated in Minang society. They are not only regarded as the owner of family’s properties, but also as the backbone of family in term of economy. Recently, their role is going to develop in public area along with their political participation either in local or national context. Though the term of bundo kanduang is still recognized within Minang society, but its understanding no longer reflect its ideal meaning. In daily life, bundo kanduang refers to to the pattern of behavior and function in term of matrilineal society. The role and status of bundo kanduang is going to change in term of household life, kaum as well as society which finally cause to the emergence of dualism understanding of bundo kanduang.Keywords : Perubahan, peranan bundo kanduang, dan masyarakat Minangkabau modernCopyright © 2011 by Kafa`ah All right reservedDOI : 10.15548/jk.v1i1.46